Global stroke statistics 2022. Issue 9 (October 2022) - Thayabaranathan, Tharshanah; Kim, Joosup; Cadilhac, Dominique A; Thrift, Amanda G; Donnan, Geoffrey A; Howard, George; Howard, Virginia J; Rothwell, Peter M; Feigin, Valery; Norrving, Bo; Owolabi, Mayowa; Pandian, Jeyaraj; et al.
Background: Contemporary data on stroke epidemiology and the availability of national stroke clinical registries are important for providing evidence to improve practice and support policy decisions. Aims: To update the most current incidence, case-fatality, and mortality rates on stroke and identify national stroke clinical registries worldwide. Methods: We searched multiple databases (based on our existing search strategy) to identify new original papers, published between 1 November 2018 and 15 December 2021, that met ideal criteria for data on stroke incidence and case-fatality, and added these to the studies reported in our last review. To identify national stroke clinical registries, we updated our last search, using PubMed, from 6 February 2015 until 6 January 2022. We also screened reference lists of review papers, citation history of papers, and the gray literature. Mortality codes for International Classification of Diseases (ICD)-9 and ICD-10 were extracted from the World Health Organization (WHO) for each country providing these data. Population denominators were obtained from the United Nations (UN) or WHO (when data were unavailable in the UN database). Crude and adjusted stroke mortality rates were calculated using country-specific population denominators, and the most recent years of mortality data available for each country. Results: Since our last report in 2020, there were two countries (Chile and France) with new incidence studies meeting criteria for ideal population-based studies. New data on case-fatality were found for Chile and Kenya. The most current mortality data were available for the year 2014 (1 country), 2015 (2 countries), 2016 (11 countries), 2017 (10 countries), 2018 (19 countries), 2019 (36 countries), and 2020 (29 countries). Four countries (Libya, Solomon Islands, United Arab Emirates, and Lebanon) reported mortality data for the first time. Since our last report on registries in 2017, we identified seven more national stroke clinical registries, predominantly in high-income countries. These newly identified registries yielded limited information. Conclusions: Up-to-date data on stroke incidence, case-fatality, and mortality continue to provide evidence of disparities and the scale of burden in low- and middle-income countries. Although more national stroke clinical registries were identified, information from these newly identified registries was limited. Highlighting data scarcity or even where a country is ranked might help facilitate more research or greater policy attention in this field.